Advaita Vedanta answer to the hard problem of consciousness: A philosophical review - Ravi Kumar Reddy Juturi (Wolters Kluwer Medknow Publications, 2020)
For thousands of years, human beings have been exploring the fundamental nature of the world and the self. In this process, modern science and Vedanta philosophy do not differ in conceiving the physical body as a material and mind also as a material. But now and then, the question is asked that so-called matter is not sentient, it cannot be aware or conscious, and how does matter suddenly become conscious/aware/sentient being? For this reason, consciousness studies have become very important in the last two to three decades and it has opened up. These studies are now turn out to be multidisciplinary by the interest of brain scientists, neuroscientists, psychologists, philosophers of mind, language, physicists, computer scientists, Artificial Intelligence. A lot of work has been done in this field of science to address what is this subjective conscious experience which a human being has internally. Consciousness studies are not new in the east, about two to three thousand years ago texts called Upanishads which are originated from Vedas are clearly stated about consciousness and its nature. In this article, the nature of consciousness is discussed and demonstrated according to Advaita Vedanta Philosophy. The article also encompasses the standpoint of modern science on consciousness. Finally, an attempt is made to answer the so-called hard problem of consciousness from the Advaita Vedanta perspective.